Technology adoption among fishermen in Malaysia - Mazuki, Raidah; Man, Norsida; Omar, Siti Zobidah; Bolong, Jusang; D’Silva, Jeffrey Lawrence; Mohamed Shaffril, Hayrol Azril (Marsland Press, 2012)
Technologies have been improved as a crucial tool in developing the agriculture industry. Fisheries, one of the agriculture branches have benefited a lot from the technologies invention. Advanced tools such as sonar, echo sounder and GPS for example have been proven to have impacts on the fisheries industry particularly on the fishermen socio-economic aspects. As the technologies adoption is crucial among the fishermen, it is important to understand the factors that determine their adoption of technologies and this study attempts to reveal a number of potential impingement factors. This is a qualitative study where the discussion is made based on literature and documents analyses. Data gained have revealed that factors such as level of education, finance, extension workers’ roles, fishermen future expectation and prediction, behavioral factors and other demographic factors. It is recommended that relevant agencies to accentuate on these factors on their planning strategies and expectantly it can assist in enhancing technologies adoption among the fishermen.